Concrete slab comparison and embodied energy optimisation for alternate design and construction techniques. (1st April 2015) - Miller, Dane; Doh, Jeung-Hwan; Mulvey, Mitchell
Highlights: Embodied energy optimisation of various slab design and construction techniques. Post-tensioned slabs consumed less embodied energy in all options investigated. Steel accounts for less than 4% of weight but up to 59.6% of embodied energy. Embodied energy efficiencies lead to structural weight reductions. Abstract: Construction material consumption is greater than any time in history. Australia produces approximately 30 million tonnes of finished building products each year, with over 56% of this quantity, by mass, being attributed to concrete and a further 6%, steel. Globally, 23 trillion kilograms of concrete alone is consumed annually, with growing population driving increasing demands. This study assesses the environmental performance of various concrete slab systems. Historically, the focus of environmental performance in buildings has been Operation Energy (OE) requirements, however Zero Energy Buildings (ZEB) are changing this. Specifically the study investigates the environmental performance of concrete structures varying design parameters and construction techniques to optimise its embodied energy (EE). These structures are designed in accordance with all relevant Australian codes and standards. The various slab systems investigated include: beam & slab, flat slab and flat plates while concurrently considering the use of conventionally reinforced and post-tensioned construction methods. Designs were compared in terms of EE outcomes given fixed design criteria, with results indicating reductions between 23.7% and 49.1% when utilising post-tensioned construction methods.